The Use of Digital Financial Services by MSMEs: The Role of Financial Literacy through Trust Mediation - Christina Heti Tri Rahmawati; Harjum Muharam (Journal of Management and Entrepreneurship Research, 2026)
Objective: Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economic development, but many challenges are faced, so the psychological factor, namely trust, is needed to increase the confidence of MSME actors, which can ultimately increase the use of digital financial services and realize sustainable management strategies. This study seeks to investigate the impact of financial literacy on MSMEs' use of digital financial services in Bantul Regency, Special Region of Yogyakarta, with trust as a mediating factor. Research Design & Methods: The study included 100 MSME participants chosen through accidental sampling. Partial Least Squares Structural Equation Modeling was used to examine the data. Findings: According to the findings, financial literacy has a substantial influence on the usage of digital financial services. Furthermore, trust mediates the link between financial literacy and the use of digital financial services among MSMEs in Bantul Regency.. Implications & Recommendations: The results of this study emphasize the importance of utilizing digital financial services as a business management tool, not just a means of transaction. This strong trust will encourage MSMEs to use digital financial services more consistently for financial planning and strategic decision-making, ultimately supporting business sustainability. Future research should include a wider sample size and locations to achieve better results. Contribution & Value Added: The research contributes to MSME development projects by emphasizing that increased financial literacy and confidence in digital financial services can help people gain easier access to finance and improve competitiveness, allowing them to achieve sustainable management goals.